On the use of a multiple view interactive environment for MATLAB and octave program comprehension - Lessa, I. M. (2015)
MATLAB or GNU/Octave programs can become very large and complex and therefore difficult to understand and maintain. The objective of this paper is presenting an approach to mitigate this problem, based upon a multiple view interactive environment (MVIE) called OctMiner. The latter provides visual resources to support program comprehension, namely the selection and configuration of several views to meet developers’ needs. For validation purposes, the authors conducted two case studies to characterize the use of OctMiner in the context of software comprehension activities. The results provided initial evidences of its effectiveness to support the comprehension of programs written in the aforementioned languages.